The Effectiveness of Varying Doses of Biosaka Elicitor on The Growth and Yield Broccoli Plants (Brassica oleracea var. italica) - Lutfi Chomariyati Aprilia, Lutfi Chomariyati Aprilia; Wahidah, Fita Fitriatul (Journal of Tropical Agricultural Engineering and Biosystems - Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2024)
Broccoli (Brassica oleracea var. italica) is an annual herbaceous plant from the Brassicaceae family originating from Italy. This plant provides valuable bioactive compounds and micronutrients to the human body. This research aimed to evaluate the effectiveness of the biosaka elicitor dose and the most effective biosaka elicitor dose on the growth and yield of broccoli plants. The experiment was conducted using a completely randomized design (CRD) with 5 replications and 5 treatments, namely P 0: negative control without fertilizer, SB 1: Cow dung fertilizer 200 g/polybag + Biosaka elicitor 5 mL/L, SB 2: Cow dung fertilizer 200 g/ polybag + Biosaka elicitor 10 mL/L, SB 3: Cow dung fertilizer 200 g/polybag + Biosaka elicitor 15 mL/L, and P 1: Positive control NPK fertilizer 2 g/polybag + Phytohormone Super Gib 30 mg/L. Data were analyzed using one-way ANOVA at the 5% level and DMRT further test. The results of data analysis showed that giving the biosaka elicitor had no significant effect on plant height, number of leaves, stem diameter, time to broccoli flower crop formation, broccoli flower diameter and weight of fresh broccoli flowers. The use of cow dung fertilizer at a dose of 200 g/polybag plus a biosaka elicitor at a dose of 10 mL/L (SB 2) produced results that were not significantly effective on the growth and yield of broccoli plants with an RAE value of 4.8%.